Good night, Irene : a novel [compact disc, unabridged] - Urrea, Luis Alberto (Hachette Book Group, 2023)
In 1943, Irene Woodward enlists with the Red Cross, where she makes fast friends with Dorothy Dunford. Their time in Europe will see them embroiled in danger, from the Battle of the Bulge to the liberation of Buchenwald.